Sensation(all) Ontology - Zeiher, Cindy (Filozofski vestnik, 2023)
It is the praxis of being a subject in the world which enables psychoanalysis to theorise subjectivity. Freud theorised subjectivity from the perspective of desires, those repressed unconscious forces which conflict with the subjects’ need to live in the world. The upshot of this conflict for the subject is trauma and for psychoanalysis such trauma provides a way into a remedy, a cure, the presumption of psychoanalysis being that through its method of transference, it does indeed possess the knowledge to pursue a remedy. Lacan offers a new interpretation of Freud by considering the subject as an ongoing ontological enigma in so far as subjective unconscious desire is not only (potentially) traumatic but necessarily (always) linguistic. How is this an ontological enigma? For Lacan the subject is first and foremost a speaking being engaged in an ongoing struggle to articulate unconscious desire. This is because, claims Lacan, we are born into language which not only pre-exists us but continues after death. In this way subjectivity is inescapably oriented to language as simultaneously intrinsic external to it. The unconscious is therefore a mixture of inside and outside, an enigmatic (pre)ontological space which Lacan calls extimacy. This essay seeks to explore Lacan’s orientation of the subject towards extimacy as the site of subjective conflict where, in its quest for the subject’s desire to know and handle the symptom, transference engages a new ontological dimension in which we can say that the extimate is structured like a sensation.